Amazonian fruits with potential effects on COVID‐19 by inflammaging modulation: A narrative review - Manica‐Cattani, Maria F.; Hoefel, Ana L.; Azzolin, Verônica F.; Montano, Marco A. Echart; Cruz Jung, Ivo E.; Ribeiro, Euler E.; Azzolin, Vitória F.; Cruz, Ivana B. M. (Journal of food biochemistry, 2022)
The COVID‐19 pandemic had a great impact on the mortality of older adults and, chronic non‐ transmissible diseases (CNTDs) patients, likely previous inflammaging condition that is common in these subjects. It is possible that functional foods could attenuate viral infection conditions such as SARS‐CoV‐2 (severe acute respiratory syndrome coronavirus 2), the causal agent of COVID‐19 pandemic. Previous evidence suggested that some fruits consumed by Amazonian Diet from Pre‐Colombian times could present relevant proprieties to decrease of COVID‐19 complications such as oxidative‐cytokine storm. In this narrative review we identified five potential Amazonian fruits: açai berry (Euterpe oleracea), camu‐camu (Myrciaria dubia), cocoa (Theobroma cacao), Brazil nuts (Bertholletia excelsa), and guaraná (Paullinia cupana). Data showed that these Amazonian fruits present antioxidant, anti‐inflammatory and other immunomodulatory activities that could attenuate the impact of inflammaging states that potentially decrease the evolution of COVID‐19 complications. The evidence compiled here supports the complementary experimental and clinical studies exploring these fruits as nutritional supplement during COVID‐19 infection. Practical applications These fruits, in their natural form, are often limited to their region, or exported to other places in the form of frozen pulp or powder. But there are already some companies producing food supplements in the form of capsules, in the form of oils and even functional foods enriched with these fruits. This practice is common in Brazil and tends to expand to the international market. Amazonian fruits have bioactive molecules, which present antioxidant activity, modulate inflammatory cytokines and assist in tissue regeneration and functions. Thus, they can help reduce the clinical complications caused by aging and aggravated by COVID‐19, and may even decrease SARS‐COV‐2 infection.